2012
DOI: 10.1017/s0021932011000769
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and Homosexuality

Abstract: Summary. The origin of preferences and values is an unresolved theoretical problem in behavioural sciences. The Savanna-IQ Interaction Hypothesis, derived from the Savanna Principle and a theory of the evolution of general intelligence, suggests that more intelligent individuals are more likely to acquire and espouse evolutionarily novel preferences and values than less intelligent individuals, but general intelligence has no effect on the acquisition and espousal of evolutionarily familiar preferences and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The Savanna‐IQ Interaction Hypothesis (13, 14) proposes that, because general intelligence evolved to solve evolutionarily novel problems, more intelligent individuals may be more likely to acquire and espouse evolutionarily novel preferences and values that our ancestors did not possess than less intelligent individuals are. Thus, relative to their less intelligent counterparts, more intelligent children are more likely to grow up to espouse the evolutionarily novel values of left‐wing liberalism or atheism (13); to be nocturnal (15); to consume the evolutionarily novel substances of alcohol, tobacco, and psychoactive drugs (16); to prefer evolutionarily novel instrumental music such as classical and light music (17); and regardless of their genetic and hormonal predisposition, to engage in evolutionarily novel homosexual behavior (18).…”
Section: Introductionmentioning
confidence: 99%
“…The Savanna‐IQ Interaction Hypothesis (13, 14) proposes that, because general intelligence evolved to solve evolutionarily novel problems, more intelligent individuals may be more likely to acquire and espouse evolutionarily novel preferences and values that our ancestors did not possess than less intelligent individuals are. Thus, relative to their less intelligent counterparts, more intelligent children are more likely to grow up to espouse the evolutionarily novel values of left‐wing liberalism or atheism (13); to be nocturnal (15); to consume the evolutionarily novel substances of alcohol, tobacco, and psychoactive drugs (16); to prefer evolutionarily novel instrumental music such as classical and light music (17); and regardless of their genetic and hormonal predisposition, to engage in evolutionarily novel homosexual behavior (18).…”
Section: Introductionmentioning
confidence: 99%
“…The second refers to a petroglyph of Bardal, Norway, dating back to the Mesolithic period. According to Nash [ 16 ], “ Two of the human figures are locked in ‘rear-entry’ sexual intercourse ”, although this interpretation has been challenged, as the sex of the smaller and penetrated individual is not identifiable [ 21 ]. When we inspected the depiction of the petroglyphs from the original reports [ 80 – 82 ], we identified several problems due to the variability in drawings.…”
Section: Resultsmentioning
confidence: 99%
“…Some could argue that anthropologists have failed to detect MHP in some societies because it was negatively sanctioned or taboo. This could be true in some cases; however, as mentioned by [ 21 ], these same anthropologists have also described negatively sanctioned behaviors such as murder, theft, infanticide and extramarital affairs. Thus, the documented absence of MHP in some societies, where other taboo behaviors were nevertheless uncovered, suggests that MHP may often be absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that gay men and feminine boys have higher intelligence levels on average, which may be due to the fact that more intelligent people are more likely to develop childhood gender nonconformity (Money and Epstein, 1967;Weinrich, 1978). Kanazawa (2012) used data from three large, nationally representative samples (two of which are prospectively longitudinal) from the United States and the United Kingdom. The author concluded that, on average, more intelligent individuals are more likely to identify themselves as homosexual, experience homosexual attraction, engage in homosexual behavior and have more homosexual cohabitation partners than less intelligent individuals.…”
Section: Introductionmentioning
confidence: 99%